Expert System Application Design for Diagnosing Damage to The Charger Rectifier Panel with A Website-Based Forward Chaining Method - Firman Robianto; Entis Sutrisna (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
In the increasingly complex world of work, as technology and information continue to evolve, there is a need for a medium that can leverage information to support business processes or activities in an organization, making them more effective and efficient. PT. Swadaya Engineering, a company operating in the electrical and telecommunications industry located in South Jakarta, is facing a problem of frequent damage reports on rectifier charger panels that are difficult to convey manually through phone calls. This constraint is a hindrance to improving the effectiveness and efficiency of the company, causing customer dissatisfaction due to a lack of information obtained. To address this issue, the author developed an expert system application for diagnosing rectifier charger panel damage based on a website using forward chaining as the application development method. The purpose of designing this application is to improve the effectiveness and efficiency of the company in delivering information on rectifier charger panel damage and increasing customer satisfaction in diagnosing such damage. It is expected that this expert system application will be an effective medium for the company to leverage information and support business processes or activities that are carried out.